FACTORS AFFECTING HEALTHCARE DEMAND IN VIETNAM DURING COVID-19 - Anh Nguyen Ngoc (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
According to statistics of the Ministry of Health of Vietnam, the proportion of people infected with the disease has been increasing recently. In addition, according to the statistics of the General Statistics Office of Vietnam, the budget and spending on health tend to increase. That means there is an increase in people's health care needs. The main objective of the study is to examine the factors affecting health care in Vietnam. The study used initial survey data in Nam Dinh, where GDP per capita is equivalent to 96.4% of the national average GDP, with a total of 500 respondents. Respondents were selected based on convenience sampling, the questionnaires were designed according to previous studies and added a research variable on COVID-19, and took place in July 2021. Descriptive analysis and linear regression statistics were used with with the help of SPSS software. Result shows that factors such as income, age, education, participation in health insurance, belief in healthcare, effects of COVID-19, family medical history and self-perceived health status were statistically significant in influencing the need for medical care. According to the study results, public health authorities and governments should pay attention to targets to increase the use of health care.